1985
DOI: 10.1084/jem.162.3.1105
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of type II collagen-induced arthritis by in vivo treatment with anti-L3T4.

Abstract: Type II collagen-induced arthritis (CIA) in mice and rats is an inflammatory polyarthritis that displays several characteristics similar to human rheumatoid arthritis (1, 2). The onset of CIA is associated with the development of both a cellular and humoral response to type II collagen (3) and is restricted in mice to animals of the H-2 q or H-2 r haplotype (4). The humoral response to type II collagen appears to be an essential element in the development of the disease although the role of cellular immunity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
128
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(141 citation statements)
references
References 12 publications
12
128
0
1
Order By: Relevance
“…CD4 MAb have been shown to be effective in experimental transplantation studies (19) and in the treatment of autoimmune disease in animal models (3,4). It has been suggested that temporary blockade of the CD4 receptor could lead to a state of tolerance (19).…”
Section: Van Der Lubbe Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 MAb have been shown to be effective in experimental transplantation studies (19) and in the treatment of autoimmune disease in animal models (3,4). It has been suggested that temporary blockade of the CD4 receptor could lead to a state of tolerance (19).…”
Section: Van Der Lubbe Et Almentioning
confidence: 99%
“…the treatment of autoimmune diseases in experimental animal models (3,4), open-label studies were performed in patients with RA (5)(6)(7)(8)(9)(10)(11)(12). CD4 MAb treatment was well tolerated and induced a rapid amelioration of arthritis activity in the majority of the patients studied.…”
mentioning
confidence: 99%
“…In these models, it has been shown that both cellular and humoral immunity play a role in the pathogenesis of this experimental disease (9,lO). The antibody response to CII is under the control of the major histocompatibility complex (MHC) (1 I), and CIA cannot be induced in animals with either inherited or experimentally impaired T cell function (12)(13)(14).…”
Section: Erck Caroline a D Botman Margreet Jonker And Bert A 'Tmentioning
confidence: 99%
“…For that reason, animal experiments are required to optimize immunomodulatory protocols and to identify the mechanism of operation of an anti-CD4 MoAb. On the other hand, several studies have been performed on collagen-induced arthritis (CIA) in mice using anti-CD4 MoAbs [15][16][17], and although these treatments were found to prevent the induction of CIA, they were ineffective in ameliorating established arthritis.…”
Section: Introductionmentioning
confidence: 99%